Keikhlasan Survivor Bencana Tsunami dan Gempa Aceh - Nashori, Fuad (Unisia, 2016)
This articlemnsto elaborating the results of study on the consciousness of the survivors the earthquake and tsunami disasters in Aceh. The study using interview and observation methods, reveals that the survivors have some such consciousnesses as: spiritual conciousness; psychological readiness; self reliance to shoulder any life burden; God forgiveness seeking; life meaning seeking; positive thinking; regretting of the past; surrendering to God and seeking God help. The study also shows some factors affecting the consciousness of the survivors, such as: faiths, knowledges, experiences, and family supports.